The safety of cefepime and ceftazidime in pediatric oncology patients1. Issue 5 (4th February 2013) - Hoffman, James M.; Frediani, Jamie; Herr, Michael; Flynn, Patricia M.; Adderson, Elisabeth E.
Abstract Background Concern has been raised about possible increased mortality associated with the use of cefepime. There are limited data available on the pragmatic use of beta‐lactam antibiotics, especially in children. Procedure This retrospective study included 532 pediatric oncology patients. The outcomes of patients treated with cefepime for suspected serious bacterial infections were compared to those of patients treated with ceftazidime. Primary outcomes included 30‐ and 90‐day all‐cause mortality. Results The demographic and clinical characteristics of 337 patients treated with ceftazidime were similar to those of 195 patients receiving cefepime. Thirty‐day and 90‐day all cause mortality rates were comparable (30‐day OR for cefepime: 3.48, 95% CI 0.31–38.84, P = 0.3; 90‐day OR: 0.99, 95% CI 0.29–3.42, P = 1.0). There were also no differences in infection‐related mortality rates, secondary infections, or adverse drug events. Deaths occurring within 30 days of hospitalization were judged to be attributable to infection, but not the result of treatment failure or adverse drug events. Deaths occurring between 30 and 90 days were associated with progressive or new malignancy. Secondary infection was significantly associated with mortality. Conclusions The use of cefepime in pediatric oncology patients is not associated with increased mortality when compared to ceftazidime, however the small number of deaths in this study limits the strength of this conclusion. Previous associations between antimicrobial therapy and increased all‐cause mortality may have been confounded by patients' demographic characteristics and co‐morbid conditions. All‐cause mortality may be an insensitive outcome for studies examining the efficacy and safety of these agents. Pediatr Blood Cancer 2013; 60: 806–809. © 2013 Wiley Periodicals, Inc.